Self‐Repairable, High Permittivity Dielectric Elastomers with Large Actuation Strains at Low Electric Fields. (16th March 2015) - Dünki, Simon J.; Ko, Yee Song; Nüesch, Frank A.; Opris, Dorina M.
Abstract : A one‐step process for the synthesis of elastomers with high permittivity, excellent mechanical properties and increased electromechanical sensitivity is presented. It starts from a high molecular weight polymethylvinylsiloxane, P1, whose vinyl groups serve two functions: the introduction of polar nitrile moieties by reactingP1 with 3‐mercaptopropionitrile (1 ) and the introduction of cross‐links to fine tune mechanical properties by reactingP1 with 2, 2′‐(ethylenedioxy)diethanethiol (2 ). This twofold chemical modification furnished a material, C2, with a powerful combination of properties: permittivity of up to 10.1 at 10 4 Hz, elastic modulus Y 10% = 154 kPa, and strain at break of 260%. Actuators made ofC2 show lateral actuation strains of 20.5% at an electric field as low as 10.8 V μm –1 . Additionally, such actuators can self‐repair after a breakdown, which is essential for an improved device lifetime and an attractive reliability. The actuators can be operated repeatedly and reversibly at voltages below the first breakdown. Due to the low actuation voltage and the large actuation strain applications of this material in commercial products might become reality. Abstract : A one‐step process is presented for the synthesis of dielectric elastomers with permittivity of up to 10.1 at 10 kHz, Y(10%) = 154 kPa, and strain at break of 260%. Actuators made with them are able to self‐repair after a breakdown and show lateral strains of up to 20.5% at an electric field as low as 10.8 V µm –1 .